2006
DOI: 10.1097/01.mph.0000212985.33941.d8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Survival in a Cohort of Predominantly Hispanic Children With Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia (ALL), the most common malignancy in children, constitutes 25% of all pediatric cancer. Childhood cancer patients who are obese at diagnosis represent a particular challenge for the oncologist. Obesity may complicate chemotherapy dose determination, and has been associated with decreased overall and event-free survival in a number of adult cancer patients, and more recently in pediatric patients. The purpose of the present study was to examine whether obesity at diagnosis was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Of note, the study included a predominantly Hispanic population on the basis of institutional demographics (n 5 157/198 [79.3%]). As previously reported nationally 27 and in a recent ALL population, 28 obesity was more prevalent in our cohort in the Hispanic population. Consistent with national averages, obesity was more prevalent in our cohort in males, 27 adolescents (particularly †A single patient with unknown cytogenetics was excluded from this analysis.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Of note, the study included a predominantly Hispanic population on the basis of institutional demographics (n 5 157/198 [79.3%]). As previously reported nationally 27 and in a recent ALL population, 28 obesity was more prevalent in our cohort in the Hispanic population. Consistent with national averages, obesity was more prevalent in our cohort in males, 27 adolescents (particularly †A single patient with unknown cytogenetics was excluded from this analysis.…”
Section: Resultssupporting
confidence: 71%
“…The adverse impact of obesity beginning at time of diagnosis on EFS and disease-related mortality has been demonstrated across multiple studies in pediatric ALL, [2][3][4][5]28 adult ALL, 39 and other hematologic malignancies. [40][41][42] The newly identified effect of obesity to increase risk for persistent MRD raises the question of whether obese patients should be considered as a higher risk group from time of diagnosis, analogous to adolescents, who could potentially benefit from more intensive therapy during induction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that showed that baseline BMI was not associated with outcome included small numbers of patients in BMI subgroups, or only analyzed the influence of being overweight on survival. [5][6][7][8]13 Studies that reported baseline undernourishment as a determinant of impaired survival were mostly conducted in developing countries or had small numbers in the BMI subgroups. [9][10][11] In those series, patients were, in addition to their disease status and treatment, also coping with additional risk factors for poor outcome such as malnutrition and poor socioeconomic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies in pediatric ALL showed contradictory results, i.e. some studies show that weight at diagnosis does not influence survival, while others suggest that being underweight or overweight at diagnosis of ALL has an influence on survival [4][5][6][7][8][9][10][11][12][13][14] (Table 1). Body composition changes extremely during the treatment of pediatric ALL due to the use of corticosteroids, 15,16 but also due to other factors such as the catabolic effect of the disease itself, stress, 17 nutritional changes and impaired exercise capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the studies acknowledged that their failure to detect an association between BMI and ALL outcome may have been due to small sample size (16, 17). Interestingly, the risk estimates of overall survival and event-free survival from both studies showed a trend of worsened outcome in the overweight/obese patients.…”
Section: Does Obesity Directly Increase Leukemia Mortality?mentioning
confidence: 99%